2018
DOI: 10.1371/journal.pone.0193484
|View full text |Cite
|
Sign up to set email alerts
|

AHR2 required for normal behavioral responses and proper development of the skeletal and reproductive systems in zebrafish

Abstract: The aryl hydrocarbon receptor (AHR) is a conserved ligand-activated transcription factor required for proper vertebrate development and homeostasis. The inappropriate activation of AHR by ubiquitous pollutants can lead to adverse effects on wildlife and human health. The zebrafish is a powerful model system that provides a vertebrate data stream that anchors hypothesis at the genetic and cellular levels to observations at the morphological and behavioral level, in a high-throughput format. In order to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 60 publications
5
67
0
Order By: Relevance
“…However, analysis of zebrafish behavior is far more variable between laboratories. Nonetheless, consistent with previous reports that TCDD is teratogenic (Carney et al, 2006) and causes abnormal behavior in larval zebrafish (Garcia et al, 2018), we detected TCDD as a hit for both endpoints. Similarly, in accordance with Noyes et al (2015), we identified BDE-99, BDE-47, BPDP, TPhP, TCEP, and TCPP as causing hypoactivity in the photomotor behavior assay at 5 dpf.…”
Section: Comparison Of Hits To Existing Zebrafish Datasupporting
confidence: 92%
“…However, analysis of zebrafish behavior is far more variable between laboratories. Nonetheless, consistent with previous reports that TCDD is teratogenic (Carney et al, 2006) and causes abnormal behavior in larval zebrafish (Garcia et al, 2018), we detected TCDD as a hit for both endpoints. Similarly, in accordance with Noyes et al (2015), we identified BDE-99, BDE-47, BPDP, TPhP, TCEP, and TCPP as causing hypoactivity in the photomotor behavior assay at 5 dpf.…”
Section: Comparison Of Hits To Existing Zebrafish Datasupporting
confidence: 92%
“…Maternal zygotic embryos could be derived from homozygous ahr1 single and double mutant parents with natural spawning. In contrast, natural spawning was not observed in ahr2 mutant embryos, consistent with previous studies reporting reduced fertility in ahr2 mutants (Garcia et al, 2018). ahr2 mutant embryos were therefore generated from incrosses of heterozygous ahr2 mutant parents, which demonstrated normal fecundity.…”
Section: Generation Of Aryl Hydrocarbon Receptor Mutant Zebrafishsupporting
confidence: 89%
“…ahr2 mutant embryos were therefore generated from incrosses of heterozygous ahr2 mutant parents, which demonstrated normal fecundity. Previously published zebrafish ahr mutants are highlighted in Figure 1 for comparison (Garcia et al, 2018;Goodale et al, 2012;Sugden et al, 2017).…”
Section: Generation Of Aryl Hydrocarbon Receptor Mutant Zebrafishmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine significant differences between three treatment group data were analyzed using a one-way ANOVA with Tukey post hoc test (P-value < 0.05, statistically significant) with GraphPad Prism 4 software (La Jolla, CA). Significant differences were calculated with two-way ANOVA and Tukey post hoc test or a repeated measures two-way ANOVA and Tukey post-hoc test (P-value < 0.05, statistically significant) when both treatment and another condition, like water condition, zone of tank, or a behavioral stimulus, was present 38 . For the shuttle box assay a linear regression was fitted to the data for each treatment to generate initial time and rate of learning graphs, while a separate analysis of variance (AOV) followed by a Tukey's statistical difference was used to calculate statistical significance amongst the groups 34 .…”
Section: Discussionmentioning
confidence: 99%